Speaking up about the labor code: A survey of employed and unemployed in Panama - Dean Spinanger (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1986)
In the first part of this project the Labor Code (LC) in Panama was analyzed with respect to its impact on the demand for labor. This entailed firms (i.e., employers) being surveyed in connection with their views about the implications of the LC. Specifically they were requested to respond to the following general questions: How has the LC affected their employment/remuneration policies? How did they perceive specific parts of the Code? How would they react to certain hypothetical changes in regulations/ policies? What would they themselves suggest in the way of modifications to or radical changes in labor market policies in Panama?
Keywords: 330; Arbeitsrecht; Arbeitsmarkt; Arbeitsmarktpolitik; Panama